Clinical study to assess influence of immediate provisionalization and various implant morphologies on implant stability: A prospective clinical study - Qi, Meiyao; Deng, Shiyong; Tan, Zhen (Frontiers in Surgery, 2023)
Introduction The aim of this study was to evaluate the influence of different implant morphologies and immediate provisionalization options on the change of implant stability. Methods 94 Patients were randomized to receive implants from Straumann® BL/Straumann® BLT/Astra OsseoSpeed® TX, meanwhile having the same opportunity to receive healing abutment or immediate provisionalization. Implant stability quotient (ISQ) and marginal bone loss (MBL) were recorded at following timepoints. Parametric statistic was used for data analysis. Results Data showed that ISQ and MBL values of conical/straight/straight with micro-thread neck implants had no significant difference. Discussion Immediate provisionalization options could move the dip point of ISQ values ahead or delayed around one week, which were also relevant to implant systems. MBL values were proved to be unaffected by both two factors mentioned above.